PROBLEMATIKA KEKUATAN POLITIK ISLAM DI YAMAN, SURIAH, DAN ALJAZAIR - Ghafur, Muhammad Fakhry (Pusat Penelitian Politik, 2015)
The wave of democratization in the Middle East today has changed the political map of the region with the emergence of the power of political Islam, in the mean of political activity based on the principles of Islam both from the point of departure, the program, agenda and objectives. Nevertheless, in some countries there is still an attitude phobia against Islam. This shows the regimeâ€™s efforts to return to authoritarianism or â€œbackward bending prossesâ€ as an example in Tunisia, Egypt, and Libya, where the military regime can return to political power. Similarly in Yemen, Ali Abdullah Salehâ€™s regime was replaced by his deputy military, Abd Rabbuh Mansur Hadi, who must be driven by the separatist movement Al-Houti. Whereas in Syria the Islamic political forces are always under attack from the regime of Bashar Al-Assad which is still in power. As for the Algerian Islamic movements like the Muslim Brotherhood and Salafiyyah, they form alliances and achieve a significant voice in the parliamentary elections in 2012 although the military regime may dominate the political life of the country. The phenomenon of the power of political Islam in Yemen, Syria, and Algeria will be the focus of this study.Keywords: Political Islam, Yemen, Syria, Algeria.